Learning motivational interviewing: prospects to preserve practitioners' well-being - Endrejat, Paul C; Kauffeld, Simone (International journal of workplace health management, 2021)
PurposeMotivational interviewing (MI) is a collaborative communication style designed to help clients achieve desired behavior changes. MI includes communication methods along with a mindset that avoids attempting to impose behavior change. Relying on the conservation of resources theory, this research report argues that learning MI helps practitioners communicate more effectively and preserve their own psychological health resources.Design/methodology/approachWe tested whether MI training resulted in beneficial effects on practitioners' resilience and burnout (i.e. exhaustion and disengagement), surveying participants (N = 42) from various disciplines who learned MI at a training institute. Subjects received a questionnaire before and one month after MI training. The post-training questionnaire also assessed whether participants applied the training content in practice.FindingsThe results revealed that the training reduced participants' disengagement. Practical application was a predictor for this decrease as well as an increase in resilience.Research limitations/implicationsDue to the small sample size and self-reported data, this paper should be considered an experimental study that could inspire future research in this area, using more elaborate research designs.Practical implicationsLearning MI not only helps in facilitating behavior change in clients but also in bolstering practitioners' own resources. MI novices should aim to apply their newly acquired skills.Originality/valueThis study is among the first to explicitly hint at the possibility that learning MI helps practitioners preserve their psychological resources.